Comparison of Serum Iron and Total Iron Binding Capacity Between Hemo and Peritoneal Dialysis Patients - Ali, B.H; Al-Mashadani, Z.I (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In  this  study,  20  patients  were  selected    having  renal  failure  .10 patients  were  hemo&  10  peritoneal  dialysis  procedure. Patients  had been  given  r HuEPO    subcutaneous with supplement of Iron  dextran after  di alysis  . Hemoglobin  Hb  concentration Hematocrit(Hct),serum I ron ,total  Iron  binding  capacity,     transferrin  saturation percent  Ts%&    Serum    ferritin    were   measured.    Non    significant    changes    in hemoglobin, hematocrit,                                 serum  Iron ,totallron binding  capacity,transferrin saturation but a significant  difference  in serum ferritin  was found ,this was a cribed to :1-  The blood lost i n the peritoneal  or hemodialysis for access .2-   Some  patients  had  been  given  blood  to treat  anemia  or givenIron supplements which  leads to Iron overload.